Do Big Five Personality Measures of Executives and Non-Executives affect their Job Satisfaction Similarity? Perspective of Sri Lankan Large Scale Apparel Industry - kottage, H. (My University, 2016)
Many research studies on the topic of the relationship between Big Five Personality and job satisfaction concerned the single category of workers. However, there are no empirical findings about how Big Five Personality affect the job satisfaction of two different categories of employees in similar context. This study is to investigate the relationship between Big Five Personality on job satisfaction involving 293 executives and non-executives in the Sri Lankan apparel sector. Correlation and regression analyses were hired to analyses the data and the major finding of the study is that the relationship and correlation of the Big Five Personality and its dimensions on the job satisfaction are relied on different employee categories when they are working in similar organizational context.
Keywords: Job Satisfaction; Big Five Personality; Executives; Non-Executives